Shipping and a~“Great Transformation”—some remarks for a~new sustainability paradigm - Lars Stemmler (Sustainability Management Forum, 2020)
Shipping contributed significantly to facilitating global trade over the last decades. However, there is growing concern that the global economic model, in which shipping is integrated, or rather shipping contributes to, pushes the Earth towards its sustainable physical limits. There is also concern that it leads economics to dominate a~majority of human interaction. Addressing global environmental and social sustainability requires shipping to discuss its underlying economic paradigm. Both, environmental and social consequences cannot be mitigated through ever more efficiencies in shipping. On the contrary, demands for higher efficiency as the domineering element of the prevailing economic paradigm create rebound effects and provide false reassurances of “carry-on-as-usual”. Calls for increased ecological as well as social sustainability ensue. These culminate in a~“great transformation” scenario in Polanyi's interpretation, which questions humankind's core economic values and mental models of growth and prosperity. These considerations result in a~call to review the economic paradigm under which shipping also operates. Such attempt outlines four elements to effect eco-social transformations.
Keywords: 650; Shipping; Great Transformation; Global value chains; Sustainability; Planetary boundaries